Improved antimicrobial activity and bioactivity of porous CaP–TiO2 coating through surface nanofunctionalisation. (May 2015) - Yu, L.; Li, J.; Wang, D.; Ouyang, L.; Jin, G.; Liu, X.
Abstract : Titanium based implant materials are confronting poor osteointergtation and bacterial infection issues when giving full play its desirable mechanical properties to hard tissue replacement applications. On the basis of plasma electrolytic oxidation (PEO) synthesised porous CaP–TiO2 coatings, which possess favourable biological performance but poor antimicrobial potential, in this work, surface nanofunctionalisation was performed using hydrothermal treatment in order to endow these coatings with antimicrobial ability. After surface nanofunctionalisation, the coatings were decorated with numerous nanoscale petal-like topography without obviously changing the original PEO synthesised porous structure and anatase titania predominant phase composition. The effects of antibacterial evaluation suggest that the nanofuntionalised CaP–TiO2 coating possessed excellent antimicrobial activity against both Escherichia coli and Staphylococcus aureus species. The antimicrobial efficacies were all close to 100% compared to untreated PEO coating. After immersion in simulated body fluid for 7 days, the hydrothermal treated coatings were fully covered by dense hydroxylapatite layers, while untreated PEO coating was not, indicating their enhanced bioactivity.